2021
DOI: 10.1371/journal.pone.0251907
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of open- and closed-skill exercise on cognition and peripheral proteins: A cross-sectional study

Abstract: Previous research indicates that different exercise modes might create different effects on cognition and peripheral protein signals. This study aimed to compare the effects of long-term participation in an open and closed-skill exercise on cognitive functions and Brain-derived neurotrophic factor and Cathepsin B levels. 18 fencers, 18 swimmers, 18 sedentary controls between 18–25 years old participated in the study. Participants performed visuospatial working memory, verbal fluency and selective attention tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 59 publications
(67 reference statements)
1
24
1
Order By: Relevance
“…Regarding the differences by type of sport, we found that sport type is closely linked to visual attention, with tracking accuracies on the MOT task among basketball athletes being markedly better than those in both the closed skill sport group and the non-athlete group. A plausible explanation for this finding is that open skill athletes have to monitor numerous changing stimuli and continuously shifting positions to excel in their sport (Ong, 2017;Gökçe et al, 2021). In basketball, players have to allocate visual attention to track the targets of the ball, teammates, and opponents while inhibiting irrelevant information over time on the court.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the differences by type of sport, we found that sport type is closely linked to visual attention, with tracking accuracies on the MOT task among basketball athletes being markedly better than those in both the closed skill sport group and the non-athlete group. A plausible explanation for this finding is that open skill athletes have to monitor numerous changing stimuli and continuously shifting positions to excel in their sport (Ong, 2017;Gökçe et al, 2021). In basketball, players have to allocate visual attention to track the targets of the ball, teammates, and opponents while inhibiting irrelevant information over time on the court.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, AE training programs of moderate-to-vigorous intensities for at least 16-weeks demonstrate increases in circulating CTSB in both healthy and cognitively impaired populations [ 24, 31 ]. A unique study by Gökçe et al [ 60 ] examined CTSB responses in a mixed sport, highly trained endurance athlete cohort (average VO 2 max of ∼55 ml/kg/min), and a control cohort (average VO 2 max of ∼45 ml/kg/min) where circulating CTSB was increased in response to moderate intensity exercise by 27– 55% in the athlete groups but only 17% in the control cohort. In parallel to the data presented herein, the non-athlete, recreationally active cohort did not achieve an elevated CTSB response to moderate intensity aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
“…One study had no exercise intervention and assessed the effects of long-term sport participation activity (from 7 to 50 years) (De la Rosa et al, 2019). One study assessed both the effects of long-term exercise (from 5 to 10 years) and acute aerobic exercise (40 minutes, moderate intensity) performed by the same participants (Gokce et al, 2021). One study assessed an acute exercise effect (field hockey match) (Malcolm et al, 2022).…”
Section: Exercise Characteristicsmentioning
confidence: 99%